TWO CONCEPTIONS OF POLITICAL AUTHORITY: AUGUSTINE, DE CIVITATE DEl, XIX. 14–15, AND SOME THIRTEENTH-CENTURY INTERPRETATIONS - Markus, R. A. (The journal of theological studies, 1965)
R. A. MARKUS; TWO CONCEPTIONS OF POLITICAL AUTHORITY: AUGUSTINE, DE CIVITATE DEl, XIX. 14–15, AND SOME THIRTEENTH-CENTURY INTERPRETATIONS, The Journal of Theolo